Factors influencing somatic embryogenesis, regeneration, and Agrobacterium-mediated transformation of cassava (Manihot esculenta Crantz) cultivar TME14 - Nyaboga, Evans N.; Njiru, Joshua M.; Tripathi, Leena (Frontiers in Plant Science, 2015)
Routine production of large numbers of transgenic plants is required to fully exploit advances in cassava biotechnology and support development of improved germplasm for deployment to farmers. This article describes an improved, high-efficiency transformation protocol for recalcitrant cassava cultivar TME14 preferred in Africa. Factors that favor production of friable embryogenic calli (FEC) were found to be use of DKW medium, crushing of organized embryogenic structures (OES) through 1-2 mm sized metal wire mesh, washing of crushed OES tissues and short exposure of tyrosine to somatic embryos; and transformation efficiency was enhanced by use of low Agrobacterium density during co-cultivation, co-centrifugation of friable embryogenic calli (FEC) with Agrobacterium, germination of paramomycin resistant somatic embryos on medium containing BAP with gradual increase in concentration and variations of the frequency of subculture of cotyledons. By applying the optimized parameters, FEC were produced for cassava cultivar TME14 and transformed using Agrobacterium strain LBA4404 harboring the binary vector pCAMBIA2301. About 70–80 independent transgenic lines per ml settled cell volume (SCV) of friable embryogenic calli were regenerated on selective medium. Histochemical GUS assays confirmed the expression of gusA gene in transformed calli, somatic embryos and transgenic plants. The presence and integration of the gusA gene were confirmed by PCR and Southern blot analysis, respectively. RT-PCR analysis of transgenic plants confirmed the expression of gusA gene. This protocol demonstrates significantly enhanced transformation efficiency over existing cassava transformation protocols and could become a powerful tool for functional genomics and transferring new traits into cassava.